Argentina, Harrison Forman on shore of Beagle Channel near stranded boat in Ushuaia - Forman, Harrison, 1904-1978 (1954)
Ushuaia - Harrison Forman (trench coat). Harbor of southernmost town in the world less than 3 hours by air from Antarctica. Southernmost tip of S. [South] America. Color Box 7